Enhanced unipolar electrical fatigue resistance and related mechanism in grain-oriented Pb(Mg1/3Nb2/3)O3-Pb(Zr, Ti)O3 piezoceramics. (10th May 2023) - Liu, Linjing; Yang, Bin; Lv, Rui; Kou, Qiangwei; Yang, Shuai; Xie, Hang; Sun, Yuan; Chang, Yunfei; Zhang, Shan-Tao; Li, Fei
Highlights: Tailoring grain orientation along [001]c greatly enhanced unipolar fatigue endurance. Achieved 230% higher and unipolar fatigue-resisted d 33 * in textured PMN-PZT ceramics. Much lower γ s ∼4% developed in the textured ceramics after 10 6 unipolar cycling. Mechanisms for the greatly enhanced unipolar fatigue resistance were explored. Abstract: Piezoceramics with high and fatigue-resisted piezoelectric properties are strongly desired for actuator applications. In this work, textured Pb(Mg1/3 Nb2/3 )O3 -Pb(Zr, Ti)O3 ceramics with Lotgering factor F 001 ∼98% were fabricated by templated grain growth technique. Strong [001]c -grain orientation ( f ∼90% and r ∼0.22) of the textured ceramics effectively produced about 230% enhanced piezoelectric coefficient d 33 * (i.e., S max / E max ) and substantially improved unipolar electrical fatigue resistance. Unipolar polarization P max and d 33 * of the textured ceramics were nearly maintained up to 10 6 unipolar cycles, while 19% and 14% degradations were respectively observed from randomly oriented counterparts. Especially, normalized d 33 * of the textured ceramics shows better unipolar fatigue resistance than those of piezoceramics reported previously. Much lower bipolar strain asymmetry γ s (∼4%) was observed from the textured samples fatigued after 10 6 unipolar cycles as compared to γ s ∼23% for randomly oriented counterparts. While charged defect accumulation model described the serious fatigue deteriorations in randomly oriented ceramics, the current work revealed that substantially enhanced unipolar fatigue resistance of the textured ceramics is mainly associated with the inherent fatigue anisotropy, weakened local bias fields owing to both enhanced domain mobility and lower defect density near grain boundaries/interfaces, and increased intrinsic contribution due to more tetragonal content. These superior characteristics suggest the great potential of textured ceramics for high-performance and robust actuator applications. Graphical abstract: Image, graphical abstract